После похорон: роман, рассказы / Агата Кристи - Кристи Агата (Серия "Детективов "Версия"", 1991)
Экземпляры: ф. 1 (20090303) / Инвентарный номер: 93983 / Цена: 20.00 / Авт.знак: К 82 / ГРНТИ: 17.82 / ББК: 84(4Вел)